WOMEN'S REBELLION IN FERDOWSI'S SHAHNAMEH - Roghaye Habibi, Abdollah Toloei-Azar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Rebellion is one of the founding principles of Iranian myths and epics arising from the struggles between eternal dualities and conflicts of good and evil. This article aims to review the rebellion of women in the Ferdowsi's Shahnameh. The research method is descriptive-analytical. The article concludes that human rebellion requires some means and components to justify it. The components widely used in epics include avenge, ambition, and love, each initiating rebellion by men and women.